Effects of chronic treadmill training on body mass gain and visceral fat accumulation in overfed rats - Dantas,E.M. (2010)
This study evaluated the effects of chronic treadmill training on body mass gain and visceral fat accumulation in overfed rats. Overfeeding was induced by reducing the litter size to 3 male pups per mother during the suckling period. The litter size of control rats was adjusted to 10 male pups per mother. Seven weeks after birth overfed and normally fed rats were selected and assigned to a sedentary protocol or to a low-intensity treadmill training protocol (60 min, 5 times/week, for 9 weeks). Four groups (overfed sedentary, N = 23; normally fed sedentary, N = 32; overfed exercised, N = 18, and normally fed exercised, N = 18) were evaluated at 18 weeks. Data are reported as means ± SEM. Initial body weight was similar in control and overfed rats [8.0 ± 0.2 g (N = 42) vs 8.0 ± 0.1 g (N = 50); P > 0.05] and body weight gain during the suckling period was higher in the overfed rats (30.6 ± 0.9 vs 23.1 ± 0.3 g; P < 0.05). Exercise attenuated the body weight gain of overfed compared to sedentary rats (505 ± 14 vs 537 ± 12 g; P < 0.05). The sedentary overfed rats showed higher visceral fat weight compared to normally fed animals (31.22 ± 2.08 vs 21.94 ± 1.76 g; P < 0.05). Exercise reduced visceral fat by 36.5% in normally fed rats and by 35.7% in overfed rats. Exercise attenuated obesity in overfed rats and induced an important reduction of visceral fat.